2021
DOI: 10.1111/ijcp.14113
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of antibiotic prescribing and appropriateness for respiratory tract infections in a teaching hospital in Jordan

Abstract: Background Inappropriate use of antibiotics is a public health concern that promotes antibiotic resistance globally. This study aimed to investigate the patterns of antibiotic prescribing for respiratory tract infections (RTIs) in Jordan to encourage judicious antibiotic prescribing. Methods The researchers conducted a retrospective secondary analysis of oral antibiotics prescribed in the family medicine clinics in a teaching university hospital in Jordan in 2017. Antibiotic prescribing rates and the types of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 52 publications
2
5
0
Order By: Relevance
“…Our study found that penicillins were the predominant class of antibiotics prescribed, and these are typically from the ‘access’ group, followed by cephalosporins, and fluoroquinolones, similar to an earlier study in Zambia and Jordan, where penicillins were the most widely prescribed antibiotics, 65 , 128 with studies in Botswana, Cameroon, Ghana and Tanzania also showing high rates of prescribing of amoxicillin. 86 , 99 , 117 , 120 This was followed by metronidazole and ciprofloxacin, again similar to Botswana, Cameroon, Ghana and Tanzania.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our study found that penicillins were the predominant class of antibiotics prescribed, and these are typically from the ‘access’ group, followed by cephalosporins, and fluoroquinolones, similar to an earlier study in Zambia and Jordan, where penicillins were the most widely prescribed antibiotics, 65 , 128 with studies in Botswana, Cameroon, Ghana and Tanzania also showing high rates of prescribing of amoxicillin. 86 , 99 , 117 , 120 This was followed by metronidazole and ciprofloxacin, again similar to Botswana, Cameroon, Ghana and Tanzania.…”
Section: Discussionsupporting
confidence: 89%
“…This outcome aligns with findings from other studies, where RTIs were the most common conditions in which antibiotics were often prescribed. 99 , 116 , 128 , 129 A similar study conducted in Lusaka, Zambia also reported that most antibiotics were prescribed for RTIs. 74 …”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…(29.1%) and Acinetobacter spp. (29%) were discovered to be the two most common microorganisms in Jordan [ 24 ]. In contrast to these investigations, E. coli (41%) was the most common bacterium to be isolated, followed by Klebsiella pneumoniae (45%), Klebsiella freundii (1.3%), Citrobacter freundii (2.1%), Streptococcus agalactiae (2.1%), P. aeruginosa (16%), and Serratia liquefaciens (2.1%) [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…To determine the prevalence of AMR and antibiotic misuse, and to address the problem of Gram-negative bacterial resistance in patients admitted to tertiary hospitals, a study from Jordan [ 24 ] showed that the most prevalent and resistant pathogen in patients was P. aeruginosa . Nitrofurantoin, meropenem, and imipenem were more effective against infections caused by E. coli .…”
Section: Discussionmentioning
confidence: 99%